Individuation and the transformation of society through the intersection of the Jungian approach and quantum physics - de Souza , Cristiane Bergmann (Seven Editora, 2023)
It is not what we see that rules the world, what commands the world is the unconscious. Jung once said that "until you become conscious, the unconscious will direct your life and you will call it destiny." Every day, you do not have to go very far to be able to perceive and feel the coldness, the indifference, the hunger, the social inequality, the racism, the homophobia, the religious intolerance, the violence in the urban centers practiced by those who are supposed to protect us, the domestic violence, the destruction of the forests, the abandonment to the very fate of the indigenous tribes persecuted and murdered by illegal loggers and miners in the Amazon, the corruption in politics and the unpreparedness and inconsequence of the government creating other crises in the country, in addition to the crisis caused by the pandemic. The time of destruction that man has become accustomed to – that has become "normal" – to perform or to live in the daily life of the world. DOI:https://doi.org/10.56238/alookdevelopv1-142